University students' perspectives on tobacco control in the Asia-Pacific: a content analysis of a case competition. Issue 5 (3rd September 2021) - Withers, Mellissa; Nguyen, Alexandra; McCool, Judith
ABSTRACT: The Asia-Pacific region has the highest number of active smokers in the world. Efforts to reduce tobacco use should implement evidence-based measures. The Association of Pacific Rim Universities is a non-profit network of more than 50 universities representing 18 economies. In 2017, it held a virtual global health case competition relating to the use of universities as platforms for tobacco control. This study is a content analysis of tobacco control proposals submitted by 24 teams from 10 economies. Content analysis of the 10-min videos examined (1) general tone and scope of videos; (2) contextual analysis; (3) intervention approaches; (4) theoretical framework; (5) primary versus secondary prevention; (6) individual versus structural approaches. Proposals were not comprehensive; most included some but not all elements recommended by the WHO FCTC. Smoking was often referred to as a 'habit' (instead of an addiction), which likely explains the predominance of individual-level behavior change interventions (smoking cessation) over structural interventions (tobacco ad or sales bans). The most common intervention was the enforcement of current bans on smoking (proposed in 78% of videos), perceived as a major barrier to tobacco control. While most proposals emphasized individual components (e.g. health education and peer support), some also proposed to create more supportive smoke-free environments through billboards, posters and cues to action, such as 'no smoking' reminders and signs with cessation hotline numbers. University faculty, students and campus-wide organizations are well positioned to lead tobacco control efforts. More work is needed to support the establishment of smoke-free campus environments.